Age-Specific Modulation of Prefrontal Cortex LTP by Glucocorticoid Receptors Following Brief Exposure to HFD - Shrivastava, Kuldeep; Rosenberg, Tali; Meiri, Noam; Maroun, Mouna (Frontiers in Synaptic Neuroscience, 2021)
The corticolimbic circuits in general and the medial prefrontal cortex in particular, undergo maturation during juvenility. It is thus expected that environmental challenges in forms of obesogenic diet can exert different effects in juvenile animals compared to adults. Further, the relationship between glucocorticoids and obesity has also been demonstrated in several studies. As a result, glucocorticoid receptor (GR) antagonists are currently being tested as potential anti-obesity agents. In the present study, we examined the effects of short-term exposure to high-fat diet (HFD) on prefrontal long-term potentiation (LTP) in both juvenile and adult rats, and the role of glucocorticoid receptors (GRs) in modulating these effects. We found HFD impaired prefrontal LTP in both juveniles and adults, but the effects of GR modulation were age- and diet-dependent. Specifically, the GR antagonist RU-486 reversed the impairment of LTP in juvenile animals following HFD, and had no effect on control-diet animals. In adult animals, RU-486 has no effect on HFD-impaired LTP, but abolished LTP in control-diet animals. Furthermore, impairments in the prefrontal LTP following HFD are involved with an increase in the mPFC GR levels only in the juveniles. Further, we found that in vivo application of GR agonists into adult mPFC rescued HFD-induced impairment in LTP, suggesting that these receptors represent strategic therapeutic targets to potentially combat obesity in children exposed to a Western diet.